1992
DOI: 10.1099/00221287-138-2-269
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of extracellular mutacin, a bacteriocin from Streptococcus sobrinus

Abstract: Mutacin MT6223, a cell-free bacteriocin produced by S?reptococcus sobrinus MT6223, was purified by ammonium sulphate precipitation, chromatofocusing with PBE 94 and column chromatography on SP Sephadex C-25. The specific activity of the purified mutacin was increased 1950-fold with a recovery of 9.7 %. The molecular mass of the purified mutacin preparation was estimated to be 6-5 kDa. The mutacin activity was stable from pH 2-7, and was resistant to treatment at 100 "C for 20 min. It was inactivated by papain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…In the initial studies of SA-FF22 it was demonstrated that this bacteriocin is active against many strains of related streptococci and only certain gram-positive bacteria (57). Bacteriocins of members of the mutans streptococcal group have been found to be active against other members of the mutans group, several gram-positive and gram-negative bacterial pathogens, including representative strains of Staphylococcus spp., Actinomyces spp., Clostridium spp., Neisseria spp., L. monocytogenes, and Helicobacter pylori (19,31,34,38,40), and strains that are resistant to nisin and antibiotics such as vancomycin (37). Finally, salivaricin A was also found to be active against M. luteus T-18 (52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the initial studies of SA-FF22 it was demonstrated that this bacteriocin is active against many strains of related streptococci and only certain gram-positive bacteria (57). Bacteriocins of members of the mutans streptococcal group have been found to be active against other members of the mutans group, several gram-positive and gram-negative bacterial pathogens, including representative strains of Staphylococcus spp., Actinomyces spp., Clostridium spp., Neisseria spp., L. monocytogenes, and Helicobacter pylori (19,31,34,38,40), and strains that are resistant to nisin and antibiotics such as vancomycin (37). Finally, salivaricin A was also found to be active against M. luteus T-18 (52).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies of streptococcin SA-FF22 indicated that this lantibiotic is stable at acidic pHs but not at alkaline pHs (57). Mutacin MT6223 is also stable at a pH range from 2 to 7 and is resistant to treatment at 100°C for 20 min; although it retains activity even after 3 months at 4°C or in a frozen state, it looses 50% of its activity after 4 weeks of storage at room temperature (31). Finally, mutacin II was found to be stable and biologically active over a wide range of pH values (pH 4 to 10) or after heat treatment at 100°C for 30 min (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of myricetin on DNA and protein synthesis were investigated by assaying the ability of B. cepacia to incorporate the respective radiolabel precursors into trichloroacetic acid (TCA) -precipitable materials (Loyola-Rodriguez et al, 1992). Briefly, B. cepacia 91.452 was grown in Tryptic Soy broth to an optical density at 600 nm of 0.1 (ca.…”
Section: [ 3 H]-thymidine and [ 3 H]-serine Incorporation Assaysmentioning
confidence: 99%
“…Despite of the efforts to optimise broth composition, enhance the growth of microorganisms and prevent contamination during procedures, the methodology is time-consuming and the microbial viability is essential to confirm the presence pathogens. Cell killing and degradation by bacteriocin as well as degradation of DNA by proteolytic enzymes and endonucleases has been demonstrated in several studies (Loyola-Rodriguez et al 1992, Cowman & Baron 1993, Cascales et al 2007). These substances may cause deleterious effects on the peri-implant support tissues.…”
Section: Conventional Culturesmentioning
confidence: 95%